Alloy precursor composite material and preparation method thereof, tantalum aluminum alloy and preparation method thereof
By adopting the alloy front -drive composite material in high -strength aluminum alloy, the nano -nitride powder and aluminum alloy in situ reaction are modified under the action of laser effect to form a nano -enhanced phase AL3TA, which solves the performance The problem of less improvement has achieved significant mechanical performance improvement and decreased defects.
Patent Information
- Application Number
- CN202410806877.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-21
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-06-21
AI Technical Summary
In the laser additive manufacturing process, high-strength aluminum alloys have problems such as poor powder melting fluidity, oxide inclusion, formation of thick columnar crystal structures, and thermal cracks, resulting in less performance improvement.
Use the composite material of the alloy pre -drive body to modify the nano aluminum nitride powder on the surface of the powder, and react with the aluminum alloy in situ under the action of laser to form a nano -enhanced phase AL3TA and N2, significantly refine the grain, resist crack expansion , And reduce defects such as pores.
It significantly improves the mechanical properties of alloy, including the improvement of stretch strength and extension, and reduced cracks and pore defects, and improved overall performance.
Smart Images

Figure CN118751936B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of alloy materials, and in particular to an alloy precursor composite material and a preparation method thereof, a tantalum aluminum alloy and a preparation method thereof. Background Art
[0002] High-strength aluminum alloys, characterized by low density, high specific strength, and excellent processability, are widely used in aerospace, automotive, and consumer electronics industries. With the continuous development of modern industry, higher requirements are being placed on the comprehensive performance of aluminum alloy structural components, such as lightweight, high strength, high toughness, and corrosion resistance. Al-Zn alloy, as an ultra-high-strength, hard aluminum alloy, is widely used in aerospace load-bearing components such as rocket compartments and aircraft fuselages due to its excellent processability, excellent corrosion resistance, and high specific stiffness.
[0003] The development of laser additive manufacturing (LAM) technology offers a new approach for designing new materials and structures, achieving diverse performance and multifunctionality. Unlike traditional metal subtractive and isotropic processing, LAM utilizes a high-energy laser beam, using powder as the raw material. Computer-controlled lasers scan the powder layer by layer to form the part, ultimately achieving a near-net shape. Laser AM offers a high degree of design and manufacturing freedom, theoretically unrestricted by complex shapes. However, the metal materials suitable for LAM are currently quite limited.
[0004] Aluminum alloy materials, especially high-strength aluminum alloy materials such as Al-Zn alloys, have the following problems when they are used for laser additive manufacturing: (1) High-strength aluminum alloys have high element content and high reflectivity to laser, resulting in poor powder melting fluidity; (2) High-strength aluminum alloys inevitably encounter oxygen during the laser forming process, which easily forms oxide inclusions; (3) High-strength aluminum alloys have a wide solidification and crystallization temperature range, which easily forms coarse columnar crystal structure, resulting in poor strength and toughness; (4) Under the instantaneous action of high-energy laser, the melt undergoes extreme cold and hot cycles, resulting in large shrinkage stress during cooling, which exceeds the inherent strength of the material, easily generates thermal cracks, and causes a sharp decrease in strength and toughness.
[0005] Currently, improving the formability of Al-Zn alloys in laser additive manufacturing is mainly achieved through alloy composition design, such as adding ceramic powder to form a reinforcement phase. However, when ceramic powder is added to Al-Zn alloy metal powder, problems such as uneven dispersion of ceramic powder and cracks at the interface between ceramic and alloy matrix are prone to occur, resulting in little improvement in the performance of the Al-Zn alloy produced by laser additive manufacturing. Summary of the Invention
[0006] The present invention aims to address the technical problems to be solved by the present invention, which address the deficiencies of the prior art. The present invention provides an alloy precursor composite material, a preparation method thereof, and a tantalum-aluminum alloy and a preparation method thereof. In the present invention, the alloy precursor composite material, under the action of a laser, dissolves aluminum nitride powder in the modified tantalum powder in a molten pool, reacting in situ with the aluminum alloy to form nano-reinforced phases of Al3Ta and N2. The nano-reinforced Al3Ta phase significantly refines the grains and resists crack propagation. The escape of N2 under the disturbance of the high-temperature molten pool reduces defects such as porosity, ultimately achieving improved mechanical properties.
[0007] According to a first aspect of the present invention, the present invention provides an alloy precursor composite material, comprising aluminum alloy powder and modified tantalum powder, wherein the modified tantalum powder is tantalum powder surface-modified with aluminum nitride powder; the particle size of the aluminum alloy powder is larger than the particle size of the modified tantalum powder, and the particle size of the aluminum nitride powder is less than or equal to 100 nm; the mass ratio of the modified tantalum powder to the aluminum alloy powder is 0.1:19.9 to 1:49, and the amount ratio of the aluminum nitride powder to the tantalum powder is 2:1 to 4:1.
[0008] Preferably, the mass ratio of the modified tantalum powder to the aluminum alloy powder is 1:99, and the amount of matter ratio of the aluminum nitride powder to the tantalum powder is 3:1.
[0009] Preferably, the particle size of the aluminum alloy powder is 15 μm to 53 μm, the particle size of the modified tantalum powder is 1 μm to 5 μm, and the particle size of the aluminum nitride powder is 20 nm to 100 nm.
[0010] Preferably, the aluminum alloy powder includes Al-Zn alloy powder, and the Al-Zn alloy powder includes 5% to 10% Zn, 1% to 2% Cu, 2% to 3% Mg in terms of mass percentage, with the balance being Al.
[0011] According to a second aspect of the present invention, the present invention provides a method for preparing an alloy precursor composite material, the preparation method comprising the following steps:
[0012] Modifying the surface of the tantalum powder with aluminum nitride powder by infiltration to obtain modified tantalum powder;
[0013] The modified tantalum powder is blended with aluminum alloy powder to obtain an alloy precursor composite material.
[0014] According to a third aspect of the present invention, the present invention provides a tantalum aluminum alloy, comprising an aluminum alloy base phase, wherein a reinforcement phase tantalum aluminum is distributed within the aluminum alloy base phase, and the size of the reinforcement phase tantalum aluminum does not exceed 100 nm.
[0015] Preferably, the shape of the reinforcement phase tantalum aluminum oxide includes a spherical shape.
[0016] According to a fourth aspect of the present invention, a method for preparing a tantalum-aluminum alloy is provided, wherein the aluminum nitride powder in the tantalum powder is modified by laser melting and decomposition to obtain an intermediate phase tantalum, and the intermediate phase tantalum reacts in situ with the aluminum alloy to form a reinforcing phase Al3Ta alloy.
[0017] Preferably, the laser melting comprises the following steps:
[0018] Using 3D modeling software to build a 3D model of the part, and using slicing software to slice the 3D model into layers and set laser processing parameters to obtain 2D slice data of the 3D model, and then importing the 2D slice data into a laser additive manufacturing forming device;
[0019] The alloy precursor composite material is formed by laser additive manufacturing according to the two-dimensional slice data, and an alloy part in which the alloy base phase is distributed with the reinforcing phase Al3Ta is obtained by melting the alloy precursor composite material layer by layer.
[0020] The present invention has the following beneficial effects:
[0021] 1. In the present invention, tantalum powder modified with aluminum nitride powder with a particle size of nanometers is used. Compared with aluminum nitride powder with a particle size of micrometers, aluminum nitride powder with a particle size of nanometers has a larger specific surface area, better plasticity, and is not easy to crack during ball milling.
[0022] 2. In the present invention, the alloy precursor composite material of the present invention can fully react in situ with the aluminum matrix under the action of laser on the tantalum powder modified by the nano-aluminum nitride ceramic powder, wherein the nano-aluminum nitride ceramic is first decomposed to form free Al ions and N2, obtaining the intermediate phase tantalum. Subsequently, the nano-aluminum nitride ceramic is first decomposed to form free Al ions and the Al ions in the aluminum matrix react with tantalum to form the nano-reinforced phase Al3Ta. The nano-reinforced phase Al3Ta plays a role in dispersion strengthening, which can significantly refine the grains and resist crack propagation. The escape of N2 can play a stirring role, thereby reducing defects such as pores and achieving improved mechanical properties. At the same time, the decomposed Al element in the aluminum nitride ceramic can compensate for the part of the Al element in the aluminum matrix that reacts with tantalum, thereby ensuring the balance of the aluminum matrix system.
[0023] 3. In the present invention, the reinforcing phase Al3Ta has a higher melting point than the aluminum matrix, and can be used as a nucleating agent during the nucleation of the aluminum alloy, playing a role in grain refinement and strengthening, promoting the transformation of columnar crystals to equiaxed crystals, thereby inhibiting the initiation of matrix cracks and significantly improving the mechanical properties.
[0024] 4. The aluminum nitride ceramic powder of the present invention is infiltrated into the surface of the tantalum powder by hot isostatic pressing, so that the bonding force between the aluminum nitride ceramic powder and the tantalum powder is stronger, which can prevent the aluminum nitride ceramic powder from easily peeling off from the surface of the tantalum powder during subsequent ball milling. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The morphology of the nano-aluminum nitride ceramic powder modified tantalum powder obtained in Example 1 of the present invention is shown;
[0026] Figure 2 An optical metallographic photograph of the polished alloy part obtained in Example 1 of the present invention is shown;
[0027] Figure 3 The SEM microstructure of the alloy part obtained in Example 1 of the present invention is shown;
[0028] Figure 4 The TEM microstructure of the nano-precipitated phase of the alloy part obtained in Example 1 of the present invention is shown;
[0029] Figure 5 The tensile stress-strain curve of the alloy part obtained in Example 1 of the present invention is shown;
[0030] Figure 6 The morphology of the nano-aluminum nitride ceramic powder modified tantalum powder obtained in Example 2 of the present invention is shown;
[0031] Figure 7 An optical metallographic photograph of the polished alloy part obtained in Example 2 of the present invention is shown;
[0032] Figure 8 The SEM microstructure of the alloy part obtained in Example 2 of the present invention is shown;
[0033] Figure 9 The TEM microstructure of the nano-precipitated phase of the alloy part obtained in Example 2 of the present invention is shown;
[0034] Figure 10 The tensile stress-strain curve of the alloy part obtained in Example 2 of the present invention is shown;
[0035] Figure 11 Shows the optical metallographic photograph of the polished alloy parts obtained in the comparative example of the present invention;
[0036] Figure 12 Shown is the SEM microstructure of the alloy part obtained in the comparative example of the present invention;
[0037] Figure 13 Shown is a TEM microstructure diagram of an alloy part obtained in a comparative example of the present invention;
[0038] Figure 14 The tensile stress-strain curve of the alloy parts was obtained in the comparative example. DETAILED DESCRIPTION
[0039] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention will be described in further detail. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. That is, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments.
[0040] In the present invention, the aluminum nitride powder in the modified tantalum powder is dissolved in the molten pool under the action of laser by the alloy precursor composite material, and reacts with the aluminum alloy in situ to form nano-reinforced phases Al3Ta and N2. The nano-reinforced phase Al3Ta can significantly refine the grains and resist crack propagation. The escape of N2 under the disturbance of the high-temperature molten pool can reduce defects such as pores, ultimately achieving improved mechanical properties.
[0041] According to a first aspect of the present invention, the present invention provides an alloy precursor composite material, comprising aluminum alloy powder and modified tantalum powder, wherein the modified tantalum powder is tantalum powder surface-modified with aluminum nitride powder; the particle size of the aluminum alloy powder is larger than the particle size of the modified tantalum powder, and the particle size of the aluminum nitride powder is less than or equal to 100 nm; the mass ratio of the modified tantalum powder to the aluminum alloy powder is 0.1:19.9 to 1:49, and the amount ratio of the aluminum nitride powder to the tantalum powder is 2:1 to 4:1.
[0042] Preferably, the mass ratio of the modified tantalum powder to the aluminum alloy powder is 1:99, and the amount of matter ratio of the aluminum nitride powder to the tantalum powder is 3:1.
[0043] Preferably, the particle size of the aluminum alloy powder is 15 μm to 53 μm, the particle size of the modified tantalum powder is 1 μm to 5 μm, and the particle size of the aluminum nitride powder is 20 nm to 100 nm.
[0044] Preferably, the aluminum alloy powder includes Al-Zn alloy powder, and the Al-Zn alloy powder includes 5% to 10% Zn, 1% to 2% Cu, 2% to 3% Mg in terms of mass percentage, with the balance being Al.
[0045] In some embodiments, the aluminum alloy powder includes AlSi10Mg alloy powder.
[0046] According to a second aspect of the present invention, the present invention provides a method for preparing an alloy precursor composite material, the preparation method comprising the following steps:
[0047] Modifying the surface of the tantalum powder with aluminum nitride powder by infiltration to obtain modified tantalum powder;
[0048] The modified tantalum powder is blended with aluminum alloy powder to obtain an alloy precursor composite material.
[0049] According to a third aspect of the present invention, the present invention provides a tantalum aluminum alloy, comprising an aluminum alloy base phase, wherein a reinforcement phase tantalum aluminum is distributed within the aluminum alloy base phase, and the size of the reinforcement phase tantalum aluminum does not exceed 100 nm.
[0050] Preferably, the shape of the reinforcement phase tantalum aluminum oxide includes a spherical shape.
[0051] According to a fourth aspect of the present invention, a method for preparing a tantalum-aluminum alloy is provided, wherein the aluminum nitride in the tantalum powder is modified by laser melting and decomposition to obtain an intermediate phase tantalum, and the intermediate phase tantalum reacts in situ with the aluminum alloy to form a reinforcing phase Al3Ta alloy.
[0052] Preferably, the laser melting comprises the following steps:
[0053] Using 3D modeling software to build a 3D model of the part, and using slicing software to slice the 3D model into layers and set laser processing parameters to obtain 2D slice data of the 3D model, and then importing the 2D slice data into a laser additive manufacturing forming device;
[0054] The alloy precursor composite material is formed by laser additive manufacturing according to the two-dimensional slice data, and an alloy part in which the alloy base phase is distributed with the reinforcing phase Al3Ta is obtained by melting the alloy precursor composite material layer by layer.
[0055] Example 1
[0056] (1) A hot isostatic pressing method is used to uniformly infiltrate aluminum nitride ceramic powder into the surface of tantalum powder to obtain tantalum powder modified with aluminum nitride powder. Specifically, aluminum nitride powder and tantalum powder with a molar ratio of 3:1 are weighed and uniformly mixed. The aluminum nitride powder uses a powder with an average particle size of 50 nm, and the tantalum powder uses a spherical powder with an average particle size of 3 μm. The above mixture is placed in a mold, placed in a hot isostatic pressing furnace, and high-purity argon is introduced. The pressure is increased to 120 MPa, and the mixture is heated to 1800°C and kept warm for 3 hours. After the reaction is completed, the mixture is placed in an argon protective atmosphere and cooled to room temperature. The mixture is then placed in a ball mill filled with anhydrous ethanol for ball milling and peeling. The ball milling speed is 100 rpm and the ball milling time is 6 hours. After ball milling, the mixed solution is placed in a vacuum drying oven and dried at 80°C for 8 hours to obtain a modified powder in which the tantalum powder surface is modified with aluminum nitride powder. Figure 1 As shown, the nano-aluminum nitride powder is evenly coated on the surface of the spherical tantalum powder.
[0057] (2) The tantalum powder surface modified with aluminum nitride powder and the Al-Zn alloy powder were uniformly mixed using a German Fritsch single-tank planetary high-energy ball mill. Specifically, a ball mill and grinding balls made of Al2O3 are selected, and the ball mill and grinding balls are pretreated first. An appropriate amount of Al-Zn alloy powder is added to the ball mill, and the mass ratio of the pre-ball milling balls to the powder is 2:1, the ball milling speed is 250 rpm / s, and the ball milling time is 4 hours. After the pre-ball milling is completed, formal ball milling is started, and the mass ratio of the formal ball milling balls to the powder is 1:1. Al-Zn alloy powder and tantalum powder with a mass ratio of 99:1 and a powder modified with aluminum nitride powder on the surface are weighed and put into the pre-ball milled Al2O3 ball mill, wherein the Al-Zn alloy powder is approximately spherical and the particle size range of the Al-Zn alloy powder is 15μm to 53μm. Nitrogen is introduced into the ball mill for protection, the ball milling speed is 250 rpm / s, and the ball milling time is 6 hours. After every 20 minutes of ball milling, there is a 5-minute stop to prevent the powder temperature in the ball mill from being too high, thereby obtaining an alloy precursor composite material powder.
[0058] (3) Use UG 3D modeling software to create a cube model with dimensions of 10 mm × 10 mm × 10 mm and a rectangular parallelepiped model with dimensions of 10 mm × 8 mm × 6 mm, respectively. Save the model in STL format and import it into Magics software for slicing and laser processing parameters. The laser power is selected as 400 W, the laser scanning speed is selected as 1200 mm / s, the scanning spacing is selected as 50 μm, the powder layer thickness is selected as 40 μm, the laser spot is selected as 60 μm, the scanning strategy is selected as linear scanning strategy, and the layer spacing is selected as 67°.
[0059] (4) The alloy precursor composite material powder prepared above is processed using the SLM-100 selective laser melting equipment. Before forming, the aluminum substrate is fixed in the forming cavity, the alloy precursor composite material powder mixed in step (3) is placed in the powder cavity, and high-purity nitrogen is introduced into the equipment to make the oxygen content lower than 100 ppm. At the same time, the aluminum substrate is heated to 100°C, and finally the laser is turned on. According to the above slicing data, the target alloy parts are obtained by layer-by-layer powder spreading and layer-by-layer laser scanning and printing.
[0060] (5) After printing, the target alloy part sample obtained in step (4) is separated from the substrate by wire-cutting with electric sparks, and a cube sample with a size of 10 mm × 10 mm × 10 mm is prepared according to the standard metallographic process. After grinding and polishing, an optical metallographic photograph of the alloy sample formed by laser additive manufacturing in situ reaction reinforcement and toughening is obtained through a metallographic microscope, as shown in FIG. Figure 2 As shown in Figure 2, the sample is dense and has no defects such as cracks. The polished surface was then etched with Keller reagent for SEM microstructure observation. Figure 3 As shown in Figure 2, the microstructure is a fine equiaxed grain structure. Through TEM phase analysis, as shown in Figure 2, the microstructure is a fine equiaxed grain structure. Figure 4As shown, it was found that a large amount of uniformly distributed reinforcing phase Al3Ta nano-spherical powder with a size of less than 100nm was formed in the aluminum alloy matrix, and the reinforcing phase Al3Ta played a dispersion strengthening role.
[0061] (6) A rectangular specimen with a size of 10 mm × 8 mm × 6 mm was machined according to the standard tensile parts of metal bars, and then a tensile test was performed using a universal testing machine with a tensile rate set at 2 mm / min. The obtained engineering stress-strain curve is shown in the figure below. Figure 5 As shown, the tensile strength is 468.7 MPa and the elongation is 12.6%.
[0062] Example 2
[0063] (1) A hot isostatic pressing method is used to uniformly infiltrate aluminum nitride ceramic powder into the surface of tantalum powder to obtain tantalum powder modified with aluminum nitride powder. Specifically, aluminum nitride powder and tantalum powder with a molar ratio of 2:1 are weighed and uniformly mixed. The aluminum nitride powder uses a powder with an average particle size of 50 nm, and the tantalum powder uses a spherical powder with an average particle size of 3 μm. The above mixture is placed in a mold, placed in a hot isostatic pressing furnace, and high-purity argon is introduced. The pressure is increased to 150 MPa and the mixture is heated to 2000°C and kept warm for 2 hours. After the reaction is completed, the mixture is placed in an argon protective atmosphere and cooled to room temperature. The mixture is then placed in a ball mill filled with anhydrous ethanol for ball milling and peeling. The ball milling speed is 100 rpm and the ball milling time is 6 hours. After ball milling, the mixed solution is placed in a vacuum drying oven and dried at 80°C for 8 hours to obtain a modified powder in which the tantalum powder surface is modified with aluminum nitride powder. Figure 6 As shown, the nano-aluminum nitride powder is evenly coated on the surface of the spherical tantalum powder.
[0064] (2) A German Fritsch single-tank planetary high-energy ball mill was used to uniformly mix the powder of tantalum powder surface modified with aluminum nitride powder and Al-Zn alloy powder. Specifically, a ball mill and grinding balls made of Al2O3 were selected, and the ball mill and grinding balls were pretreated. An appropriate amount of Al-Zn alloy powder was added to the ball mill. The mass ratio of pre-ball milling balls to powder was 2:1, the ball milling speed was 250rpm / s, and the ball milling time was 4h. After the pre-ball milling was completed, the formal ball milling was started. The mass ratio of formal ball milling balls to powder was 2:1. The invention discloses a method for preparing an alloy precursor composite material comprising: a first blend of Al-Zn alloy powder and nano-aluminum nitride-coated tantalum powder in a mass ratio of 1:1, wherein the first blend of Al-Zn alloy powder and nano-aluminum nitride-coated tantalum powder in a mass ratio of 49:1 is weighed and placed in a pre-milled Al2O3 ball mill, wherein the Al-Zn alloy powder is approximately spherical and has a particle size range of 15 μm to 53 μm. Nitrogen is introduced into the ball mill for protection, the ball milling speed is 300 rpm / s, the ball milling time is 4 hours, and a 5-minute pause is performed after every 20 minutes of ball milling to prevent the powder temperature in the ball mill from being too high, thereby obtaining the alloy precursor composite material.
[0065] (3) Use UG 3D modeling software to create a cube model with dimensions of 10 mm × 10 mm × 10 mm and a rectangular parallelepiped model with dimensions of 10 mm × 8 mm × 6 mm, respectively. Save the model in STL format and import it into Magics software for slicing and laser processing parameters. The laser power is selected as 450 W, the laser scanning speed is selected as 1600 mm / s, the scanning spacing is selected as 60 μm, the powder layer thickness is selected as 30 μm, the laser spot is selected as 70 μm, the scanning strategy is selected as linear scanning strategy, and the layer spacing is selected as 37°.
[0066] (4) The alloy precursor composite material powder prepared above is processed using the SLM-100 selective laser melting equipment. Before forming, the aluminum substrate is fixed in the forming cavity, the alloy precursor composite material powder mixed in step (3) is placed in the powder cavity, and high-purity nitrogen is introduced into the equipment to make the oxygen content lower than 100 ppm. At the same time, the aluminum substrate is heated to 120°C, and finally the laser is turned on. According to the above slicing data, the target alloy parts are obtained by layer-by-layer powder spreading and layer-by-layer laser scanning and printing.
[0067] (5) After printing, the target alloy part sample obtained in step (4) is separated from the substrate by wire-cutting with electric sparks, and a cube sample with a size of 10 mm × 10 mm × 10 mm is prepared according to the standard metallographic process. After grinding and polishing, an optical metallographic photograph of the alloy sample formed by laser additive manufacturing in situ reaction reinforcement and toughening is obtained through a metallographic microscope, as shown in FIG. Figure 7 As shown in the figure, the sample is dense and has no defects such as cracks. The polished surface was then etched with Keller reagent for microstructural observation. Figure 8 As shown in Figure 2, the microstructure is a fine equiaxed grain structure. Through TEM phase analysis, as shown in Figure 2, the microstructure is a fine equiaxed grain structure. Figure 9 As shown, it was found that a large amount of uniformly distributed reinforcing phase Al3Ta nano-spherical powder with a size of less than 100nm was formed in the aluminum alloy matrix, and the reinforcing phase Al3Ta played a dispersion strengthening role.
[0068] (6) A rectangular specimen with a size of 10 mm × 8 mm × 6 mm was machined according to the standard tensile parts of metal bars, and then a tensile test was performed using a universal testing machine with a tensile rate set at 2 mm / min. The obtained engineering stress-strain curve is shown in the figure below. Figure 10 As shown, the tensile strength is 424.2 MPa and the elongation is 10.5%.
[0069] Example 3
[0070] (1) Using hot isostatic pressing to uniformly infiltrate aluminum nitride ceramic powder into the surface of tantalum powder to obtain aluminum nitride powder modified tantalum powder, specifically, weighing aluminum nitride powder and tantalum powder in a mass ratio of 2:1 and uniformly mixing them, the aluminum nitride powder using a particle size range of 20nm to 100nm, and the tantalum powder using a spherical powder using a particle size range of 1μm to 5μm, placing the above mixture in a mold, placing it in a hot isostatic pressing furnace, introducing high-purity argon gas, pressurizing it to 100MPa, heating it to 1500℃ and keeping it warm for 3h, after the reaction is completed, placing the mixture in an argon protective atmosphere and cooling it to room temperature, then placing the mixture in a ball milling jar filled with anhydrous ethanol for ball milling and peeling, the ball milling speed is 100rpm, the ball milling time is 6h, and after ball milling, the mixed solution is placed in a vacuum drying oven and dried at 80℃ for 8h to obtain a modified powder in which the tantalum powder surface is modified with aluminum nitride powder, such as Figure 7 As shown, nano-aluminum nitride is evenly coated on the surface of spherical tantalum powder.
[0071] (2) The obtained tantalum powder surface modified with aluminum nitride powder was uniformly mixed with Al-Zn alloy powder using a German Fritsch single-tank planetary high-energy ball mill. The specific steps were as follows: a ball mill and grinding balls made of Al2O3 were selected, the ball mill and grinding balls were pretreated, an appropriate amount of Al-Zn alloy powder was added to the ball mill, the pre-ball milling ball to powder mass ratio was 2:1, the ball milling speed was 250rpm / s, the ball milling time was 4h, and the formal ball milling was started after the pre-ball milling was completed. The ball milling balls and powder mass ratio were 2:1, the ball milling speed was 250rpm / s, and the ball milling time was 4h. The ratio is 1:1, and Al-Zn alloy powder and tantalum powder with aluminum nitride powder modified on the surface in a mass ratio of 19.9:0.1 are weighed and put into a pre-ball-milled Al2O3 ball mill jar, wherein the Al-Zn alloy powder is approximately spherical and the particle size of the Al-Zn alloy powder is 15μm~53μm. Nitrogen is introduced into the ball mill jar for protection, the ball milling speed is 300rpm / s, the ball milling time is 5h, and the ball milling is stopped for 5min every 20min to prevent the powder temperature in the ball mill jar from being too high, to obtain an alloy precursor composite material powder.
[0072] (3) Use UG 3D modeling software to create a cube model with dimensions of 10 mm × 10 mm × 10 mm and a rectangular parallelepiped model with dimensions of 10 mm × 8 mm × 6 mm. Save the model in STL format and import it into Magics software for slicing and laser processing parameters. The laser power is selected as 450 W, the laser scanning speed is selected as 1400 mm / s, the scanning spacing is selected as 40 μm, the powder layer thickness is selected as 70 μm, the laser spot is selected as 50 μm, the scanning strategy is selected as linear scanning strategy, and the layer spacing is selected as 37°.
[0073] (4) The alloy precursor composite material mixed powder prepared above is processed using the SLM-100 selective laser melting equipment. Before forming, the aluminum substrate is fixed in the forming cavity, the alloy precursor composite material powder mixed in step (3) is placed in the powder cavity, and high-purity nitrogen is introduced into the equipment to make the oxygen content lower than 100 ppm. At the same time, the aluminum substrate is heated to 110°C, and finally the laser is turned on. According to the above slicing data, the target alloy parts are obtained by layer-by-layer powder spreading and layer-by-layer laser scanning and printing.
[0074] Comparative Example
[0075] Al-Zn alloy powder was printed using the same printing method as in Example 1 to obtain alloy part samples. The optical metallographic photographs of the obtained alloy samples are shown in Figure 2. Figure 11 As shown, there are many defects such as cracks and pores inside the sample. Then the polished surface was corroded with Keller reagent for microstructural observation. The metallographic structure obtained is as follows Figure 12 As shown in Figure 2, the microstructure is a coarse columnar grain structure. Through TEM phase analysis, as shown in Figure 2, the microstructure is a coarse columnar grain structure. Figure 13 As shown in Figure 2, no reinforcement phase was found in the aluminum alloy matrix. The tensile stress-strain curve of the obtained alloy sample is shown in Figure 2. Figure 14 As shown, the tensile strength is 135.3 MPa and the elongation is 0.98%.
[0076] As can be seen from Examples 1-2 and the comparative example, the preparation method of the alloy containing the in-situ reinforcing phase aluminum tantalum provided by the present invention can form a uniform reinforcing phase Al3Ta in situ in an Al alloy matrix through rapid melting and solidification using a high-energy laser. The reinforcing phase Al3Ta can serve as a nucleating agent during the nucleation of the aluminum alloy, playing a role in grain refinement and strengthening, promoting the transformation of columnar crystals to equiaxed crystals, thereby inhibiting the initiation of matrix cracks and significantly improving mechanical properties. The reinforcing phase Al3Ta is a nano-spherical powder with a particle size not exceeding 100 nm and is uniformly distributed, ensuring minimal and uniform stress between the Al3Ta and the aluminum matrix.
[0077] The alloy precursor composite material of the present invention can fully react in situ with the aluminum matrix under the action of laser on the tantalum powder modified with the nano-aluminum nitride ceramic powder, wherein the nano-aluminum nitride ceramic is first decomposed to form free Al ions and N2, obtaining the intermediate phase tantalum. Subsequently, the nano-aluminum nitride ceramic is first decomposed to form free Al ions and the Al ions in the aluminum matrix react with tantalum to form the nano-reinforced phase Al3Ta. The nano-reinforced phase Al3Ta plays a role in dispersion strengthening, which can significantly refine the grains and resist crack propagation. The escape of N2 can play a stirring role, thereby reducing defects such as pores and achieving improved mechanical properties. At the same time, the decomposed Al element in the aluminum nitride ceramic can compensate for the part of the Al element in the aluminum matrix that reacts with tantalum, thereby ensuring the balance of the aluminum matrix system.
[0078] In the present invention, after the aluminum nitride ceramic powder and tantalum powder blend is placed in a hot isostatic pressing furnace, the aluminum nitride ceramic powder and tantalum powder are slightly melted upon heating, allowing the aluminum nitride ceramic powder to penetrate the surface of the tantalum powder, rather than the aluminum nitride ceramic powder adhering to the surface of the tantalum powder. By using hot isostatic pressing to allow the aluminum nitride ceramic powder to penetrate the surface of the tantalum powder, the present invention strengthens the bonding between the aluminum nitride ceramic powder and the tantalum powder, preventing the aluminum nitride ceramic powder from easily peeling off the tantalum powder surface during subsequent ball milling.
[0079] The above-described embodiments merely represent specific implementation methods of the present application. While the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of protection of the present application. It should be noted that a person skilled in the art would be able to make numerous variations and improvements without departing from the technical concept of the present application, and all such variations and improvements fall within the scope of protection of the present application.
Claims
1. An alloy precursor composite material, characterized in that: It comprises aluminum alloy powder and modified tantalum powder, wherein the modified tantalum powder is tantalum powder with aluminum nitride powder modified on the surface; the particle size of the aluminum alloy powder is larger than that of the modified tantalum powder, and the particle size of the aluminum nitride powder is less than or equal to 100 nm; the mass ratio of the modified tantalum powder to the aluminum alloy powder is 0.1:19.9 to 1:49, and the amount ratio of the aluminum nitride powder to the tantalum powder is 2:1 to 4:
1.
2. The alloy precursor composite material according to claim 1, characterized in that: The mass ratio of the modified tantalum powder to the aluminum alloy powder is 1:99, and the amount of substance ratio of the aluminum nitride powder to the tantalum powder is 3:
1.
3. The alloy precursor composite material according to claim 1, characterized in that: The particle size of the aluminum alloy powder is 15 μm to 53 μm, the particle size of the modified tantalum powder is 1 μm to 5 μm, and the particle size of the aluminum nitride powder is 20 nm to 100 nm.
4. The alloy precursor composite material according to claim 1, characterized in that: The aluminum alloy powder includes Al-Zn alloy powder, and the Al-Zn alloy powder includes 5% to 10% Zn, 1% to 2% Cu, 2% to 3% Mg in terms of mass percentage, and the balance is Al.
5. A method for preparing an alloy precursor composite material as claimed in any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: Modifying aluminum nitride powder on the surface of tantalum powder by infiltration to obtain modified tantalum powder; The modified tantalum powder is blended with aluminum alloy powder to obtain an alloy precursor composite material.
6. A method for preparing a tantalum aluminum alloy, characterized in that: Laser additive manufacturing is performed on an alloy precursor composite material as described in any one of claims 1 to 4, and the aluminum nitride powder in the tantalum powder is modified by laser melting and decomposition to obtain an intermediate phase tantalum, and the intermediate phase tantalum reacts in situ with the aluminum alloy to form a reinforcement phase Al3Ta alloy.
7. The method for preparing a tantalum aluminum alloy according to claim 6, characterized in that: The laser melting comprises the following steps: A three-dimensional model of a part is established by using a three-dimensional modeling software, and the three-dimensional model is sliced by layers by using a slicing software and laser processing parameters are set to obtain two-dimensional slice data of the three-dimensional model, and then the two-dimensional slice data is imported into a laser additive manufacturing forming device; The alloy precursor composite material is formed by laser additive manufacturing according to the two-dimensional slice data, and an alloy part in which the alloy base phase is distributed with the reinforcement phase Al3Ta is obtained by melting the alloy precursor composite material layer by layer.
8. A tantalum aluminum alloy, characterized in that: The tantalum-aluminum alloy is prepared by the preparation method of any one of claims 6 to 7, wherein the tantalum-aluminum alloy comprises an aluminum alloy basic phase, in which a reinforcing phase tantalum-aluminum is distributed, and the size of the reinforcing phase tantalum-aluminum does not exceed 100 nm.
9. The tantalum aluminum alloy according to claim 8, characterized in that: The shape of the reinforcement phase tantalum aluminum oxide includes a spherical shape.
Citation Information
Patent Citations
Aluminum-based material and preparation method thereof
CN109706350A
Interface bonding enhanced Zn-Al-Ti2AlN biomedical material and preparation method thereof
CN109865837A